Academic Program as a Factor Influencing the Students’ Decisions-Making to Enroll at Private Higher Education Institutions: Financial Aid as Moderator using Smarts - Shamsudin, Mohd Farid; Ali, Aeshah Mohd; Ishak, Mohd Fikri; Kadir, Baharudin (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aimed to identify academic programmes as a factor that influence the students’ decision-making to enrol at a private HEI and the moderating role of financial aid within the Malaysian context of private HEIs. With respect to the objectives of study, this study targeted 23 private HEIs with university status across Kuala Lumpur and Selangor. Methodology: The underpinning theory applied in this study was Theory of Planned Behavior (TPB) applied for academic programs. Five hundred (500) questionnaires distributed at selected private HEI around Kuala Lumpur and Selangor. Respondent was first-year students (undergraduate students in their first academic semester in 2018) only. Data gathered were analyzed using PLS-SEM 3 analytical software in performing PLS-SEM. Results: The analyses outcome for structural model had confirmed that there was a positive significance relationship between AP and DM, therefore, h1 accepted. However, throughout this interaction (moderation) assessment, the study had confirmed that the moderation role of FA is non-significant, thus, rejecting the h1a. Implications: A positive significance relationship between AP and DM denoted by path coefficient of  0.37; t-value of 9.778 and p-value of 0.000. As for the interaction effect (moderating) of FA that moderate the relationship path between AP and DM was insignificant showed by path coefficient of  value -0.111, p-value of 0.190 and t-value of 1.312 (Hair, Sarstedt, & Ringle, 2017).